Can lower E-region dust particles be responsible for counter electrojet? - V. H. Kulkarni; P. Muralikrishna (Geofísica Internacional, 2008)
Ablation of meteors leaves a large number of dust particles of sizes ranging from nanometers to several micrometers in the upper mesospheric region. These dust particles can affect the equatorial E-region conductivities in several ways. Most of them remain electrically neutral and can affect the electron and ion collision frequencies, especially in the lower E- region, and thereby alter the electrical conductivity of this region. This can lift the Cowling conductivity maximum by a few kilometers making it coincide with the observed electrojet current maximum. Charged dust particles in the lower E-region can considerably reduce the electrojet current density in this region, by capturing a large number of free electrons from this region. A clear evidence for this is the large difference between the electron and positive ion number densities observed in this region by in situ probes. Positive ion densities, at times, are seen to be an order of magnitude higher than the electron number densities in the upper mesospheric region. Rocket observations have also shown the presence of dust layers in this region charged positively on top and negatively at the bottom. Such dust layers can reverse the vertical polarization field locally and can even produce the phenomenon of counter electrojet. Model calculations of the electrojet current density taking into account these effects of dust particles are presented here.